Catholic Schools for the 21st Century An Overview. [Volume I.]. - National Catholic Educational Association, Washington, DC.; National Catholic Educational Association, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1991)
Part of a six-volume series, this publication contains summaries of theme papers commissioned for the National Congress on Catholic Schools for the 21st century, Nov. 6-10, 1991. The meeting had three broad goals: (1) to communicate the story of the academic and religious effectiveness of Catholic schools to a national audience; (2) to celebrate the success of Catholic schools in the United States and to broaden support for the future; and (3) to convene an assembly of key leaders in Catholic schooling. The papers served to foster a national dialogue to clarify the current status of Catholic schools in the United States, and to develop a set of future strategies to strengthen and expand the network of Catholic schools throughout the country. Ten papers, addressing the following themes, are summarized: (1) "The Catholic Identity of Catholic Schools," with papers by James Heft and Carleen Reck; (2) "Leadership of and on Behalf of Catholic Schools," with papers by Karen Ristau and Joseph Rogus; (3) "The Catholic School and Society," with papers by John Convey and John Cummins; (4) "Catholic School Governance and Finance," with papers by Rosemary Hocevar and Lourdes Sheehan; and (5) "Political Action, Public Policy, and Catholic Schools," with papers by John Coons and Frank Monahan. (KM)
Availability: National Catholic Educational Association Publications Sales Office, Suite 100, 1077 30th Street, N.W., Washington, DC 20007-3852 ($2.50, quantity discounts).
ERIC Note: For the other volumes in this series, see SO 021 647-651.
Policymakers.
Administrators.
Practitioners.
May also be available online. Address as at 14/8/18
Keywords: Catholic Educators; Catholic Schools; Educational Development; Educational Finance; Educational History; Educational Planning; Educational Principles; Educational Trends; Elementary Secondary Education; Futures (of Society); Governance; Leadership Responsibility; Politics of Education; Public Policy; School Community Relationship; Speeches/Meeting Papers; Opinion Papers